Emergency Remote Teaching: Perceptions of College Vocational Lecturers Towards Constraints and Pedagogical Competencies - Abdul raof, Shuhada; Musta'amal @ Jamal, Aede Hatib; Harmeni, Haiza Atmareni; Rosmin, Norzanah (Journal of Technical Education and Training, 2022)
This study aims to identify the perceptions of vocational college lecturers on the constraints and pedagogical competencies that need to be possessed in delivering the curriculum when the COVID-19 pandemic hits the country. The curriculum delivery method implemented in this study is online with the emergency remote teaching (ERT) method. This study was a quantitative study that used a set of questionnaires as a research instrument. The respondents of this study consisted of 364 lecturers of vocational colleges throughout Malaysia. The data collected were analysed using the SPSS software. Multivariate analysis of variance was used to analyse the data. The results of the study found that enabling conditions factor and technological factors are the main constraints for vocational college lecturers in implementing ERT teaching. Overall, the level of lecturers’ constraints is at a moderate level. Meanwhile, the aspect of pedagogical competence of lecturers in implementing ERT is also at a moderate level. The one-way ANOVA test conducted showed that there was a significant difference between the gender factors on the constraints and the pedagogical competence of the lecturers in implementing ERT. The study is significant to Malaysian Vocational College in identifying lecturers’ perceptions of the constraints faced in implementing teaching during the COVID-19 pandemic. Besides, this study is important to identify the pedagogical competencies possessed by lecturers when implementing teaching and learning at home using ERT.